The perceptions of Zimbabwean Pharmacists of their overall job satisfaction and the factors associated with it (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Job satisfaction plays an important role in the motivation, productivity and performance of employees including pharmacists. We investigated the perceptions of Zimbabwean pharmacists of their overall job satisfaction and the factors associated with it. A random sample of 120 licensed pharmacists working in community, and hospital pharmacies and industry in Zimbabwe participated in this cross-sectional study. Pharmacists were highly satisfied with their jobs. Older pharmacists and those with more experience were more satisfied than younger ones. Pharmacists in industry had the greatest job satisfaction while those in large chain retail pharmacies had the lowest. Owners were more satisfied with their jobs than non-supervisor pharmacists. There was no significant difference in job satisfaction by gender and marital status. We conclude that although pharmacists in Zimbabwe are satisfied with their jobs in general, this is not so for young pharmacists who mainly work in retail chain pharmacies.
Keywords: Job satisfaction; pharmacy manpower; pharmacy; Zimbabwe